2016
DOI: 10.1007/s00467-016-3452-z
|View full text |Cite
|
Sign up to set email alerts
|

Prospective study on the potential of RAAS blockade to halt renal disease in Alport syndrome patients with heterozygous mutations

Abstract: Treatment with blockers of the renin-angiotensin-aldosterone system prevents progressive renal failure in AS patients with heterozygous mutations in the genes causing AS. Considerable numbers of aging AS patients on dialysis may have heterozygous mutations in these genes (present in 1 % of total population) as underlying disease. Hence, greater alertness towards timely diagnosis and therapy has the potential to prevent progressive renal failure in most-if not all-AS patients with heterozygous mutations in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 29 publications
0
17
0
2
Order By: Relevance
“…Therefore, with the help of registry data, the further positive effect of ramipril already can be predicted with great certainty in children with early stages of AS. 8,14,15,27 Baseline albuminuria was almost 2 times lower in the placebo (23 mg/gCrea) versus the ramipril (39.4 mg/gCrea) group. Therefore, more children in the placebo group needed a tripling of albuminuria to reach the primary efficacy Progression of renal disease in the randomized arm.…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, with the help of registry data, the further positive effect of ramipril already can be predicted with great certainty in children with early stages of AS. 8,14,15,27 Baseline albuminuria was almost 2 times lower in the placebo (23 mg/gCrea) versus the ramipril (39.4 mg/gCrea) group. Therefore, more children in the placebo group needed a tripling of albuminuria to reach the primary efficacy Progression of renal disease in the randomized arm.…”
Section: Discussionmentioning
confidence: 96%
“…Both had histology consistent with TBMN. Though this gene has typically been associated with recessive Alport syndrome, multiple reports (Marcocci et al 2009;Hines et al 2018;Longo et al 2002) have demonstrated that patients with heterozygous COL4A4 or COL4A3 variants can develop significant renal disease and can benefit from early initiation of renin-angiotensinaldosterone system blockade (Stock et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Patients cannot be cured, but like in other forms of glomerular disease, will benefit from timely initiated general supportive care including blood pressure control and anti-proteinuric medication [25]. More specifically, evidence is increasing that early treatment with angiotensin converting enzyme inhibitors or angiotensinogen receptor blocking agents considerably delays the progressive decline in renal function in patients with Alport syndrome [26][27][28][29][30][31][32]. Therefore, both from a counseling and a therapeutic point of view, it is important to identify patients early in life.…”
Section: Discussionmentioning
confidence: 99%